Bronchial artery embolization versus conservative treatment for hemoptysis: a systematic review and meta-analysis - Shengxin Fan; Xiaocheng Cheng; Xiaohui Wang; Yuliang Liu; Wei He; Hong Chen (BMC Pulmonary Medicine, 2024)
Abstract Background Bronchial artery embolization (BAE) is currently an important treatment for hemoptysis. However, there is no consensus in the efficacy and safety of BAE compared to conservative treatment for hemoptysis, which limits the widespread use of BAE in hemoptysis. The objective was to assess the clinical benefit of BAE versus conservative treatment in patients with hemoptysis. Methods A systematic search was conducted on the PubMed, Embase, ScienceDirect, CochraneLibrary, and ClinicalTrials up to March 2023. Both randomized controlled trials (RCTs) and cohort studies reporting rates of recurrent hemoptysis, clinical success, mortality, and complication by BAE and conservative treatment alone for hemoptysis were included. Data were pooled and compared by the use of odds ratio (OR) and 95% confidence interval (CI). Results Twelve studies (three RCTs, nine cohorts) involving 1231 patients met the eligibility criteria. Patients treated with BAE had lower recurrence rates of hemoptysis (26.5% vs. 34.6%; OR 0.37, 95% CI 0.14–0.98), higher clinical success rates (92.2% vs. 80.9%; OR 2.77, 95% CI 1.66–4.61), and lower hemoptysis-related mortality (0.8% vs. 3.2%; OR 0.20, 95% CI 0.05–0.84) compared with conservative treatment alone. There was no significant difference in all-cause mortality between the two groups. In terms of security, the incidence of major complications and minor complications in patients undergoing BAE treatment was 0.2% (1/422) and 15.6%, respectively. Conclusions BAE was more effective than conservative treatment alone in controlling hemoptysis, reducing recurrence, and decreasing hemoptysis-related mortality, with an almost negligible risk of major complications.